The Existence of Women in Sunao Katabuchi's Anime Kono Sekai no Katasumi ni - Fadli, Zaki Ainul (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
The patriarchal culture that constructs society causes the position of women to be considered low. During World War II, the position of women began to change. Women not only play a role in the domestic sphere, but also in the social sphere of society. This study aims to reveal the female positioning and self-existence of the character Urano Suzu as a woman during World War II in Japan in the anime Kono Sekai no Katasumi ni . This research uses Simone De Beauvoir's theory of existentialist feminism which includes the self and the other, the myth of women, women's existence (existencefor-self and existence-for-others). The research method uses analysis of story content by looking at sentences and images in anime related to women's existence issues. The results showed that there are two types of positioning of female characters in the anime Kono Sekai no Katasumi ni, namely being required to look according to male ideal standards, and being required to obey the concept ofÂ  Ryousaikenbo. Therefore, Suzu redefined the role and position that she had previously only as an object (the other) who was confined to the domestic environment and turned into a subject role (the self) as a member of society who actively contributed to society, namelyÂ  Kaminaganoki Rinpohan and Dai Nippon Fujinkai